Clustering Universities According to Performance Indicators and Determination of Organizational Culture Types in Clusters - Maxat Aitimbetov; Dinmukhamed Kelesbayev; Gulzhamal Koptayeva; Gulshat Zhadigerova; Assylkhan Tursyn; Aripkhan Sadykov (International Review of Management and Marketing)
This study aims to reveal the organizational culture types of state universities in Kazakhstan, to define the dominant organizational culture type and to interpret the organizational culture types in terms of performance indicators. In order to achieve this goal, statistical data collected from 29 state universities were classified using hierarchical cluster analysis and Ward’s Technique. In this context, firstly, the concept of organizational culture and its effects on organizational performance were explained in the light of literature information, then cluster analysis was conducted on universities in terms of institutional size and performance. In addition, since a data-oriented approach was preferred in this study, universities were classified based on objective data instead of predetermined criteria. Finally, SPSS 22.0 program and Organizational Culture Assessment Tool were used to analyze the validity of the obtained data and the relationships between the variables, and as a result, the organizational culture types of universities were revealed, the dominant organizational culture type among them was determined and suggestions were given based on empirical findings in the study. It is expected that the results of this study will bring different perspectives on the effect of organizational culture on performance indicators in state universities in Kazakhstan.